Ethnography and the Production of Anthropological Knowledge Essays in honour of Nicolas Peterson - Musharbash, Yasmine (ANU Press, 2011)
Professor Nicolas Peterson is a central figure in the anthropology of Aboriginal Australia. This volume honours his anthropological body of work, his commitment to ethnographic fieldwork as a source of knowledge, his exemplary mentorship of generations of younger scholars and his generosity in facilitating the progress of others. The diverse collection produced by former students, current colleagues and long-term peers provides reflections on his legacy as well as fresh anthropological insights from Australia and the wider Asia-Pacific region. Inspired by Nicolas Peterson's work in Aboriginal Australia and his broad ranging contributions to anthropology over several decades, the contributors to this volume celebrate the variety of his ethnographic interests. Individual chapters address, revisit, expand on, and ethnographically re-examine his work about ritual, material culture, the moral domestic economy, land and ecology. The volume also pays homage to Nicolas Peterson's ability to provide focused research with long-term impact, exemplified by a series of papers engaging with his work on demand sharing and the applied policy domain